2019
DOI: 10.1111/jpn.13078
|View full text |Cite
|
Sign up to set email alerts
|

Association between methylation potential and nutrient metabolism throughout the reproductive cycle of sows

Abstract: DNA methylation is an important epigenetic strategy for embryo development and survival. The one‐carbon metabolism can be disturbed by inadequate provision of dietary methyl donors. Because of the continuous selection for larger litters, it is relevant to explore if highly prolific sows might encounter periods of methyl donor deficiency throughout their reproductive cycles. This study, therefore, assesses the fluctuation(s) in methylation potential (MP) and aims to link possible methyl donor deficiencies to nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The high transformation rate of SAM into SAH indicate more frequent methylation reactions during this phase ( Bonilla et al., 2010 ). A similar result was observed in van Riet's work, which showed that the methylation potential (SAM-to-SAH ratio in plasma) of the highly prolific sows increased throughout gestation but fluctuated strongly in the period around parturition ( Van Riet et al., 2019 ). Moreover, the rate of transmethylation in pregnant women during the third trimester was higher than that of the first trimester ( Dasarathy et al., 2010 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The high transformation rate of SAM into SAH indicate more frequent methylation reactions during this phase ( Bonilla et al., 2010 ). A similar result was observed in van Riet's work, which showed that the methylation potential (SAM-to-SAH ratio in plasma) of the highly prolific sows increased throughout gestation but fluctuated strongly in the period around parturition ( Van Riet et al., 2019 ). Moreover, the rate of transmethylation in pregnant women during the third trimester was higher than that of the first trimester ( Dasarathy et al., 2010 ).…”
Section: Discussionsupporting
confidence: 87%
“…During pregnancy, gene transcription is influenced by Met supply as SAM is not only the ubiquitous methyl donor for DNA methylation and the essential regulator of chromatin function, but also participates in the biosynthesis of vital components such as phospholipids ( Rees et al., 2006 ; Bleich et al., 2014 ). Van Riet et al. (2019) observed a marked elevation of plasma SAM in sows during late pregnancy while the fetal growth rate was noticeably increased, indicating the importance of increased methyl supply during late pregnancy.…”
Section: Introductionmentioning
confidence: 86%
“…Interestingly, this general similarity in amino acid profiles was also observed in nonmammalian body compositions, with the predominant amino acids in frogs (Xenopus laevis), such as glutamine, glycine, leucine, and asparagine being generally similar to those in fish species (Engraulis encrasicholus), while methionine, histidine, and phenylalanine were scarce in both [73]. By contrast, sows are intensively using methionine as a methyl donor during lactation [74].…”
Section: Discussionmentioning
confidence: 67%